Robin and the hoods [videorecording (DVD)] - Davidson, Paul (Screenwriter); Benson, Stuart; Ewart, Darcey; Williams, Mark, 1959-; Harris, Naomie, 1976-; Christie, Gwendoline, 1978- (Shout! Factory, 2025)
Fired by her imagination, Robin is the bright-eyed leader of a group of kids, the Hoods, who love to play fantasy games on a patch of land they nickname The Kingdom. While their biggest concern is a rival gang looking to take over their domain, things get serious when plans emerge to develop the area that's their playground into a new leisure facility for the town. Faced with the ruthless spokesperson Clip-Board, Robin and her friends must find a way to save their play area before it's too late.